The Survey of Present Collecting Situation University Libraries of Shiraz City - Mehrnaz Rahmat (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2008)
The survey of present collecting situation university libraries of Shiraz city and display methods for improve quality is object of this examination. This research is a survey and questionnaire is means of provide information and it is used to analyze statistical information of descriptive method (frequency percent) and Excel program. In Interpretation of results, This research showed that %53.92 of librarians are specialists in library science in university libraries of Shiraz city, only and %93.75 of librarians have a role collecting. %75 of these libraries important to clients request for selection and provide materials and their basic method is using of books fairs. There in no independent committee for selecting books and there is not written policy for selecting books and there is in %12.5 of these libraries written policy for collecting, only. Catalogs are basic method for awareness of publish new materials in %93.75 of these libraries and %31.25 of these have exchange inter libraries, only.